Energy Dispersive EXAFS Performance Studies on Triphodalphosphine Rhodium Biphasic Catalyst for Hydrogenation and Hydroformylation of Olefins - Abdul Rahman, M.B.; Evans, J.; Neisius, T. (Asian Journal of Chemistry, 2010)
Energy dispersive EXAFS (EDE) data have been analyzed for the hydrogenation of styrene by the rhodium zwitterionic Rh(I) complexes. Rh(sulphos)(cod) and hydroformylation of 1-hexene by the Rh(sulphos)(COh using curved wave theory with ab initio phase-shifts. The derived parameters for metal compounds were in good agreement within experimental error of 0.02- 0.05 Å for the bond distances. The bond lengths in the rhodium complexes were refined at average distances of Rh-C 1.90 Å. Rh-P 2.31 Å and Rb-O 2.90 Å consistently. This is a good start for the quantitative analysis of the dispersive EXAFS techniques at variable temperatures and high pressures.